This and that: management of Tetralogy of Fallot and pulmonary vein stenosis in an infant—a case report. Issue 11 (23rd October 2021) - Scott, Christopher P; Shibbani, Kamel; Caldarone, Christopher A; McLennan, Daniel
Abstract: Background: Tetralogy of Fallot (TOF) is the most common congenital cyanotic cardiac lesion. Pulmonary vein stenosis occurs much less commonly and remains difficult to manage. It is exceedingly uncommon for a patient to have both lesions. This case highlights the diagnostic and management difficulties in an infant with these two lesions. Case summary: The patient is a 4-month-old female infant with a history of TOF status post right ventricular outflow tract stent placement who presented after a hypoxaemic event at home to 40% SpO2. Computed tomography angiography demonstrated previously undiagnosed pulmonary vein stenosis of all four veins. She underwent multiple catheter-based palliations including balloon dilations and stent placements in each pulmonary vein in order to maximize her chances of successful definitive repair. She underwent successful repair of her TOF and pulmonary vein stenosis at ten months of age. Discussion: The combination of TOF and pulmonary vein stenosis is not common, but when these lesions co-occur, they present a significant dilemma in determining the timing of surgery in order to optimize the odds of a successful outcome. This case demonstrates that serial catheter-based procedures can be valuable tools in minimizing pre-operative risk factors and highlights one strategy in determining timing of definitive surgical repair.